2017
DOI: 10.1002/jbmr.3129
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional Versus Longitudinal Change in a Prospective HR-pQCT Study

Abstract: Longitudinal studies assessing age-related changes using high-resolution peripheral quantitative computed tomography (HR-pQCT) provide novel insight compared with cross-sectional analyses. The purpose of this cohort study was 1) to determine individuals' change in HR-pQCT parameters over 5 years relative to least significant change (LSC), and 2) to evaluate if predicted rate of change from cross-sectional data is comparable to actual change from longitudinal investigation. A cohort of 466 (162 male, 304 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
55
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 37 publications
9
55
4
Order By: Relevance
“…This mechanism produces cortical remnants on the endocortical surface resembling trabecular bone which the HR‐pQCT software includes in trabecular bone . Trabecularization of the inner cortical layer results in an increase in Tb.Ar associated with the spurious stability of Tb.vBMD, which was found previously . The inclusion of thick cortical remnants results in a spurious stability of Tb.N and Tb.Th.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This mechanism produces cortical remnants on the endocortical surface resembling trabecular bone which the HR‐pQCT software includes in trabecular bone . Trabecularization of the inner cortical layer results in an increase in Tb.Ar associated with the spurious stability of Tb.vBMD, which was found previously . The inclusion of thick cortical remnants results in a spurious stability of Tb.N and Tb.Th.…”
Section: Discussionsupporting
confidence: 72%
“…(46) Trabecularization of the inner cortical layer results in an increase in Tb.Ar associated with the spurious stability of Tb.vBMD, which was found previously. (36,47) The inclusion of thick cortical remnants results in a spurious stability of Tb.N and Tb.Th. Because they are few and chaotically distributed, their inclusion has no impact on Tb.…”
Section: Discussionmentioning
confidence: 99%
“…We found that both cortical and trabecular parameters of the distal radius were associated with incident fracture, but that cortical HR‐pQCT parameters of the distal tibia were more consistent predictors of clinical fracture than trabecular parameters at this site. Studies of longitudinal change in older men have shown that both total and cortical volumetric BMD of the distal radius and tibia decrease over time, whereas there was no concurrent change in trabecular BMD . A subsequent longitudinal study in the same cohort compared fracture cases versus non‐cases (albeit limited to women only) and reported modest changes in total and cortical BMD among cases and non‐cases, but only marginal change in trabecular BMD at the distal tibia, but this study had to few fracture cases to assess whether there were differences by fracture status .…”
Section: Discussionmentioning
confidence: 73%
“…The discrepancy between our findings and finding based on younger postmenopausal women may be related to patterns of age‐related bone loss. Using cross‐sectional data, the estimated mean total decrement comparing old versus young men between the ages 20 and 90 years is 32% at the distal radius versus 22% at the tibia, thus suggesting that there may be preferential bone loss at the distal radius and this loss would be more prominent in older men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation